2003
DOI: 10.1038/sj.npp.1300328
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Amphetamine-Induced Dopamine Release by Acute Phenylalanine/Tyrosine Depletion: A PET/[11C]Raclopride Study in Healthy Men

Abstract: Acute phenylalanine/tyrosine depletion (APTD) has been proposed as a new method to decrease catecholamine neurotransmission safely, rapidly, and transiently. Validation studies in animals are encouraging, but direct evidence in human brain is lacking. In the present study, we tested the hypothesis that APTD would reduce stimulated dopamine (DA) release, as assessed by positron emission tomography (PET) and changes in [ 11 C]raclopride binding potential (BP), a measure of DA D2/D3 receptor availability. Eight h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 45 publications
(53 reference statements)
9
81
1
Order By: Relevance
“…Indeed in a recent PET imaging of TYR depletion, we found that the increase in D 2 receptor binding as measured by [ 11 C]raclopride correlated significantly with the fall in the plasma ratio of TYR and PHE to large neutral amino acids (Montgomery et al, 2003). A similar finding was reported by Leyton et al (2004) who found that the ability of TYR depletion to attenuate the decrease in [ 11 C]raclopride binding produced by d-amphetamine correlated linearly with reduction in plasma TYR levels.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed in a recent PET imaging of TYR depletion, we found that the increase in D 2 receptor binding as measured by [ 11 C]raclopride correlated significantly with the fall in the plasma ratio of TYR and PHE to large neutral amino acids (Montgomery et al, 2003). A similar finding was reported by Leyton et al (2004) who found that the ability of TYR depletion to attenuate the decrease in [ 11 C]raclopride binding produced by d-amphetamine correlated linearly with reduction in plasma TYR levels.…”
Section: Discussionsupporting
confidence: 87%
“…However, microdialysis, 29 neuroendocrine 40 and fos expression studies 60 all suggest that APTD affects DA transmission over other catecholamines. Moreover, APTD has been shown to decrease extracellular DA levels in humans as indicated by increased striatal [ 11 C]raclopride binding in imaging studies 30,61 and to increase circulating prolactin levels (indicative of reduced DA function 62 ), but to have no effect on plasma melatonin, a neuroendocrine index of noradrenergic neurotransmission. 63 Finally, the sample size of 32 participants was modest, and only women were tested.…”
Section: Limitationsmentioning
confidence: 99%
“…Acute tyrosine/phenylalanine depletion (ATPD) is a technique which has been shown to selectively decrease dopamine synthesis and release (Jaskiw and Bongiovanni, 2004;Leyton et al, 2004;McTavish et al, 1999aMcTavish et al, , 2001aMehta et al, 2005;Montgomery et al, 2003) and impair dopamine dependent cognitive processes such as working memory (Harmer et al, 2001;Harrison et al, 2004). To our knowledge, ATPD has never been used to investigate the effects of dopaminergic modulation on Stroop task performance.…”
Section: Introductionmentioning
confidence: 99%